Tunable fabrication of two-dimensional arrays of polymer nanobowls for biomimic growth of amorphous calcium carbonate - Ding, Tao. (2013)
Two-dimensional arrays of polymer nanobowls can be fabricated by an oxygen plasma etching technique. The 2D colloidal crystals made of SiO 2 @PMMA particles are fabricated by a convective self-assembly method. The oxygen plasma treatment is applied to the colloidal crystals to selectively etch the PMMA shells. Because the oxygen plasma etching proceeds in a layer-by-layer manner from top to bottom, the top parts of the PMMA shells are etched fi rst, and the silica cores are exposed to the atmosphere, which can be removed with HF, leaving the bowl-shaped PMMA shells to form 2D arrays of polymer nanobowls. The size and packing density of the nanobowl arrays can be tuned with tightly controlled etching time. The polymer nanobowl arrays can also serve as a template to direct the growth of calcium carbonate within the interstice of the nanobowls.